Житла раннього середньовіччя у Верхньому Салтові - Колода, В.В. (Археологія, 2000)
Розглянуто житлові споруди середньовічного поселення у Верхньому Салтові. Зроблено висновок щодо складу верхньосалтівського населення у ті часи. В статье собрана информация о всех известных к настоящему времени жилищах салтовской археологической культуры середины VIII—середины X вв. н. э. на поселении Верхний Салтов Харьковской обл. Согласно устоявшимся критериям анализируются конструкция и форма построек, а также выделяются этничные элементы (признаки) домостроительства. На основе рассмотренных материалов сделан вывод о присутствии на данном памятнике в раннем средневековье различных этнических групп, которые по своему происхождению связаны с Северным Кавказом (аланы), славянами (северяне) и степным населением Евразии (тюрки, болгары). We present the information about all the dwellings, known up to date, of the Saltiv archaeological culture of the mid. VIII AD — the mid. X AD at the Verkhnii Saltiv settlement of the Kharkiv region. According to the stable criteria, we analyze the constructions and forms of buildings and single out ethnic elements (signs) of house buildings. On the basis of the materials considered, we conclude about the presence of different ethnic groups at this monument in the Early Middle Ages, which are related by their origin to the North Caucasian region (the Alans), the Slavs (the Northerners), and the steppe population of Eurasia (the Turks and Bulgarians).